Glaciological and meteorological measurements in Dronning Maud Land - Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; meteorologi

Melting, runoff and the formation of frozen lakes in a mixed snow and blue-ice field in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar; Elvehøy, Hallgeir; Bøggild, Carl Egede; Sand, Knut; Liston, Glen (Journal of Glaciology, 1996)
Large-scale melting phenomena such as meltwater drainage channels and meltwater accumulation basins of frozen lakes were surveyed on the land ice mass in Jutulgryta, Dronning Maud Land, Antarctica, during the Norwegian Antarctic Research Expedition in 1989–90 (NARE 1989–90). The largest frozen lake that was observed was close to 1 km in width. These melting features were also detected in a Landsat Thematic Mapper image recorded on 12 February 1990. Then, during NARE 1993–94, a 5year glaciological programme was started in this area. In spite of negative air temperatures and the presence of a frozen ice surface, sub-surface melting and runoff were found within the uppermost metre in blue-ice fields. The sub-surface melting is a consequence of solar radiative penetration and absorption within the ice, i.e. the “solid-state-greenhouse effect”. Temperatures in blue ice were about 6°C higher than for snow. Internal melt and meltwater transport were observed throughout the 1 month of measurements. The conditions for active melting in Jutulgryta are probably marginal. A slight increase of air temperatures can result in more “classical” surface melting, whereas a cooling may disable sub-surface melting. Studies of how the extent and characteristics of the melting features change with time can be particularly valuable as indicators of climate change. This ongoing programme clearly identifies the importance of analyzing how these melting features originate, of mapping their present areal distribution, of determining how sensitive they are to climate change and of Studying changes in the past and possible changes in the future.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; NARE 1989/90; NARE 1993/94; blåis; fjernanalyse; glasiologi; klimaendringer; satellitteknologi